Severe traumatic dental injuries and oral health related quality of life of preschool children - Laís Anschau PAULI; Francine dos Santos COSTA; Cassia Cardozo AMARAL; Thiago Machado ARDENGHI; Flávio Fernando DEMARCO; Marília Leão GOETTEMS (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective: The aim of this study was to investigate the impact of severe traumatic dental injuries on the Oral Health related Quality of Life (OHRQoL) of preschool children. Methods: This cross-sectional study was conducted with children aged 2 to 5 years and their mothers, in Pelotas/ Brazil Southern. The Early Childhood Oral Health Impact Scale (ECOHIS) was applied to assess the perception of mothers about children's OHRQoL. Oral examination included dental trauma, categorized as absent/mild (enamel fracture only) or severe, the number of decayed, missing or restored primary teeth (dmft), and presence of anterior open bite. The impact of severe dental trauma on OHRQoL was evaluated using logistic regression analysis (P<0.05). Results: A total of 599 preschool children were included and 7.4% had severe dental trauma. Of these 73.3% showed negative impact on OHRQoL (p= 0.044). After adjustments, children with severe dental trauma had an impact in OHRQoL 110% higher than those without/with mild trauma (OR: 2.10, 95% CI 1.01-4.35). Severe dental injuries caused negative impact on the oral symptoms (OR: 2.13, 95% CI 1.10-4.14), psychological (OR: 2.13, 95% CI 1.10-4.13) and family function (OR: 2.79, 95% CI 1.17-6.61) domains. Conclusion: The presence of severe dental trauma impacts the OHRQoL of preschool children and their families.